Media effects - Potter, W. James (SAGE Publications, 2012)
"Media Effects offers students an in-depth examination of the media's constant influence on individuals and society. W. James Potter frames media's effects in two templates: influence on individuals and influence on larger social structures and institutions. By positioning the different types of effects in the forefront, Potter helps students understand the full range of media effects, how they manifest themselves, and the factors that that are likely to bring these effects into being. Throughout the book, Potter encourages students to analyze their own experiences by searching for evidence of these effects in their own lives, making the content meaningful on a personal level." -- Provided by publisher.